The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jrs.1444
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of synthetic crandallite‐type minerals—optical and inelastic neutron scattering spectra

Abstract: The consequences of the resulting perturbed symmetry and of the non-equivalence of the bridging m-OH groups in the Al 2 OH fragments were pointed out (complexity of the n(Al 2 O-H), d(Al 2 OH) and g(Al 2 OH) bands). The vibrations of the PO 4 and HPO 4 groups could be separated. Some aspects of the vibrational behaviour of the AlO 2 (OH) 4 units and of the layers composed therewith were addressed. The translational modes of the interlayer cations Ca 2+ and Sr 2+ could be observed; the findings support the sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…However, apatite and crandallite structures readily accept substitution of both cations and anions, and we interpret the observed correlation as evidence of the existence of a specific carbonate type of crandallite with carbonate for phosphate substitution. All absorption bands in the spectra of the crandellite-dominated samples investigated here are slightly shifted compared to those reported for pure synthetic crandallite by Breitinger et al (2006). Some diffraction peaks due to crandallite exhibit a distinct broadening at the bases and asymmetry towards low angle (e.g.…”
Section: Mineralogymentioning
confidence: 57%
See 2 more Smart Citations
“…However, apatite and crandallite structures readily accept substitution of both cations and anions, and we interpret the observed correlation as evidence of the existence of a specific carbonate type of crandallite with carbonate for phosphate substitution. All absorption bands in the spectra of the crandellite-dominated samples investigated here are slightly shifted compared to those reported for pure synthetic crandallite by Breitinger et al (2006). Some diffraction peaks due to crandallite exhibit a distinct broadening at the bases and asymmetry towards low angle (e.g.…”
Section: Mineralogymentioning
confidence: 57%
“…4). The split ν 3 carbonate bands are absent in the spectrum of synthetic crandallite (Breitinger et al, 2006). However, apatite and crandallite structures readily accept substitution of both cations and anions, and we interpret the observed correlation as evidence of the existence of a specific carbonate type of crandallite with carbonate for phosphate substitution.…”
Section: Mineralogymentioning
confidence: 69%
See 1 more Smart Citation
“…4b) and the total chemical analyses (Table 2), resulted in the identification of these minerals in the ceramic sherds from Da Mata, albeit in much smaller quantities. These phosphates can be recognized by the anti-symmetric stretching of the P-O, 1035 cm − 1 (Breitinger et al, 2006) found in the ceramic sherds from all the sites, and equivalent to variscite. Segelerite (CaMgFe(PO 4 ) 2 (OH)·4(H 2 O)) was also identified by XRD in the sherds from Monte Dourado 1 (Fig.…”
Section: Phosphatesmentioning
confidence: 98%
“…Breitinger et al 25 studied the synthetic minerals crandallite and goyazite by IR, Raman, and inelastic neutron scattering. Therein the authors have investigated the influence of disorder.…”
Section: Mineralogymentioning
confidence: 99%